A Worldwide Bibliometric Analysis of Publications on Advance Care Planning in the Past 3 Decades. (June 2020) - Liu, Chia-Jen; Yeh, Te-Chun; Hsieh, Ming-Hsuan; Woung, Lin-Chung; Huang, Sheng-Jean; Chen, Ming-chih; Liu, Chih-Kuang
Background: In recent decades, issues related to end-of-life care and advance care planning (ACP) have attracted popular attention. Advance care planning has been broadly discussed as one of the potential solutions to protect a patient's rights, autonomy, and dignity at the end of life. To better understand publishing on this topic, we conducted this study to demonstrate the worldwide research productivity, trends, and citations of ACP in the past 3 decades by bibliometric analysis. Methods: Articles published on ACP were retrieved from the Web of Science Core Collection database, and the subject terms included "advance directive, " or "advance care planning." Results: Overall, 2126 publications on ACP were retrieved until January 22, 2019. North America, Western Europe, and Australia were the most productive regions. The top 15 countries published 95.9% of the total number of articles. The United States accounted for approximately three-fifths (61.0%) of all publications. When adjusted for population size, Australia had the highest number of articles per million persons (6.64), followed by the Netherlands (6.14) and Belgium (4.61). The most productive authors were Sudore (n = 37), Deliens (n = 29), and Green (n = 24). Conclusions: The current study revealed that research in terms of publications on ACP has rapidly increased over the past 3 decades. Developed countries, especially the United States, were more concerned with the ACP research field than developing countries were.